2018
DOI: 10.3389/fnagi.2018.00245
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Cerebrospinal Fluid Barrier Gradients in Mild Cognitive Impairment and Alzheimer's Disease: Relationship to Inflammatory Cytokines and Chemokines

Abstract: Background: The pathophysiology underlying altered blood-cerebrospinal fluid barrier (BCSFB) function in Alzheimer's disease (AD) is unknown but may relate to endothelial cell activation and cytokine mediated inflammation.Methods: Cerebrospinal fluid (CSF) and peripheral blood were concurrently collected from cognitively healthy controls (N = 21) and patients with mild cognitive impairment (MCI) (N = 8) or AD (N = 11). The paired serum and CSF samples were assayed for a panel of cytokines, chemokines, and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 76 publications
2
45
1
Order By: Relevance
“…The results corresponded to a recent meta‐analysis which showed that several inflammatory markers (CRP, IL‐6, α1‐antichymotrypsin, lipoprotein‐associated phospholipase A2 and fibrinogen) are associated with an increased risk of all‐cause dementia; however, these markers were not specific for AD . Another study showed significantly elevated IL‐15, IL‐1α, and IL‐2 in combined MCI/AD serum samples . In a study, 18 predictive plasma signalling proteins (cytokines and chemokines) can be used to separate AD patients and HC with an accuracy of 90% .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The results corresponded to a recent meta‐analysis which showed that several inflammatory markers (CRP, IL‐6, α1‐antichymotrypsin, lipoprotein‐associated phospholipase A2 and fibrinogen) are associated with an increased risk of all‐cause dementia; however, these markers were not specific for AD . Another study showed significantly elevated IL‐15, IL‐1α, and IL‐2 in combined MCI/AD serum samples . In a study, 18 predictive plasma signalling proteins (cytokines and chemokines) can be used to separate AD patients and HC with an accuracy of 90% .…”
Section: Discussionsupporting
confidence: 69%
“…13 Another study showed significantly elevated IL-15, IL-1α, and IL-2 in combined MCI/AD serum samples. 24 In a study, 18 predictive plasma signalling proteins (cytokines and chemokines) can be used to separate AD patients and HC with an accuracy of 90%. 25 In addition, previous studies indicated that peripheral CRP, 26 IL-1β, 9,17 IL-6, 27 IL-12, 28 IL-18, 28,29 IL-8 30 concentrations were negatively associated with MMSE scores in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…With no changes in plasma during this time, it is suggested that CSF inflammatory responses to lumbar catheter placement vary between the AD and the control groups 20. Analysing the correlation of these marker levels with the CSF to serum albumin ratio, which is regarded as an index assessing the blood–cerebrospinal fluid barrier (BCSFB) integrity, peripheral plus central inflammatory processes were supported to play a critical role in the early changes of BCSFB function 21. This indicated a disruption of the blood–brain barrier (BBB), resulting in alterations of its permeability and transport capacity 21.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing the correlation of these marker levels with the CSF to serum albumin ratio, which is regarded as an index assessing the blood–cerebrospinal fluid barrier (BCSFB) integrity, peripheral plus central inflammatory processes were supported to play a critical role in the early changes of BCSFB function 21. This indicated a disruption of the blood–brain barrier (BBB), resulting in alterations of its permeability and transport capacity 21. Based on these, it is reasoned to speculate that the variances of specific inflammatory marker levels in body fluid may be related to that shifting distribution between the periphery and CSF.…”
Section: Discussionmentioning
confidence: 99%
“…AD patients and mouse models of AD, present increased oxidative stress and mitochondrial dysfunction, similar to that observed in senescence. These events are present in the early stages of AD and precede the major pathologic hallmarks, such as senile plaques and NFTs (Yates et al, 2015;Ott et al, 2018).…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%